2018
DOI: 10.7150/jca.20266
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Glycoprotein Non-metastatic B and Its Association with EGFR/HER2 in Gastrointestinal Cancer

Abstract: Glycoprotein non-metastatic B (GPNMB), a type I transmembrane glycoprotein, is overexpressed in melanoma and breast cancer and promotes cancer-cell invasion and motility. We previously reported cross-talk between GPNMB and human epidermal growth factor receptor 2 (HER2) in breast cancer, suggesting that GPNMB might play an important role in resistance to anti-HER2 therapy in breast cancer. Here, we clarified the association between GPNMB and HER-family proteins in gastrointestinal cancer by examining their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Transmembrane glycoprotein NMB (GPNMB) was detected in stage 3 breast cancer tissues. This finding supports Tajima et al [95], Maric et al [96], and Rose et al [97], among other studies with similar findings in malignancies including melanoma, glioma, breast cancer, and gastric cancer. On a physiological level, GPNMB improves cell invasion and motility, enabling metastasis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Transmembrane glycoprotein NMB (GPNMB) was detected in stage 3 breast cancer tissues. This finding supports Tajima et al [95], Maric et al [96], and Rose et al [97], among other studies with similar findings in malignancies including melanoma, glioma, breast cancer, and gastric cancer. On a physiological level, GPNMB improves cell invasion and motility, enabling metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…On a physiological level, GPNMB improves cell invasion and motility, enabling metastasis. It is therefore logical that, according to Tajima et al [95], a high level of GPNMB expression indicates a worse prognosis. This means that GPNMB should be recognized as an important candidate for targeted therapy of malignancies [96].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of signal transduction pathways are involved in the downstream biological effects activated by EGFR, such as RAS-RAF-MAPK, PI3K-PTEN-AKT, and JAK/STAT. Most of the above signal pathways are also involved in antibodymediated resistance to EGFR inhibition machine [17][18][19][20][21]. Any gene changes in the signaling pathway, such as KRAS, NRAS, BRAF, and PIK3CA gene mutations, may lead to the constitutive activation of EGFR and subsequent changes in intracellular signaling to eventually achieve drug resistance [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that NSBP1 plays an oncogenic role in gastric cancer. Notably, recent studies have shown that lentivirus mediated shRNA against genes with potential oncogenic role provides a new avenue for developing effective therapy for a variety of cancers 16-20. Therefore, it is promising to develop lentivirus mediated NSBP1 shRNA as a novel therapeutic approach for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%